ID-based server-aided verification signature scheme with strong unforgeability - Xiao-dong YANG; Miao-miao YANG; Guo-juan GAO; Ya-nan LI; Xiao-yong LU; Cai-fen WANG (Tongxin xuebao, 2016)
Most identity-based signature schemes in the standard model are existentially unforgeable,which cannot prevent adversaries from forging valid signatures on messages that have previously been signed.However,signature verification algorithms of ID-based signature schemes in the standard model require expensive bilinear pairing operations.In order to overcome the shortcomings of the existing ID-based signature schemes such as strong security assumption and high computation cost，a strongly unforgeable ID-based server-aided verification signature scheme was presented.This scheme was proven to be secure under collusion attacks,adaptive chosen identity and message attacks in the standard model.Analysis results show that the proposed scheme effectively reduces computation cost of pairing operation,and it greatly reduces computational complexity of signature verification algorithm.The proposed scheme is more efficient than the existing ID-based signature schemes.